Description of the puparium of Manotes plana (Diptera: Stratiomyidae: Pachygastrinae) from the Ilha da Marambaia, Mangaratiba, state of Rio de Janeiro, Brazil - Roberto de Xerez; Ana Lúcia de Freitas Lopes (Zoologia (Curitiba), 2009)
The puparium of Manotes plana Kertész, 1916 is described based on the exuviae of six larvae collected under the bark of a plant in early state of decomposition in the Ilha da Marambaia (23°04'15"S, 43°53'59", at sea level), state of Rio de Janeiro, Brazil. The external morphology and chaetotaxy is compared with the previously described puparium of Manotes crassimanus James, 1980. The texture and shape of the setae of M. crassimanus are plumose and some setae are claviform while M. plana are setiform. In M. plana the ventro-craneal furrow extends from the posterior region of the mouthparts until the median region of the head. In M. crassimanus, the furrow extends until the posterior third of the head. No diferrence occurs in position in the puparia of both species in relation of pupal respiratory spiracles.